If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -12 + -3x + -6y Solving 0 = -12 + -3x + -6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 0 + 3x = -12 + -3x + 3x + -6y Remove the zero: 3x = -12 + -3x + 3x + -6y Combine like terms: -3x + 3x = 0 3x = -12 + 0 + -6y 3x = -12 + -6y Divide each side by '3'. x = -4 + -2y Simplifying x = -4 + -2y
| f(x)=2(x-3)(x+10) | | 2/7×1/4 | | f(x)=x(2x+3)(x-1) | | 1.1z+1.2z-5.4=-10 | | 10+3x-7=5x-5+2x+8 | | 1/7v-9/5=-3/2 | | -4/7[x-14]=3/7 | | 38-8x=-4(7x+4)-6 | | 3*cos(x)+sin(x)=0 | | 8x=4.8x+10 | | 135x1502/3 | | 12x+10y=9 | | -124x^2+x^4+x=-3668 | | f=1.8(0-273.15)+32 | | 2x+3.6=7 | | V=nRT | | 2x-6=3/4 | | 5x-7x+10=4x+9+1 | | X(3)=1/729 | | X(3)=8/125 | | 0.66x-7=11 | | X(3)=8/5 | | 3x-4-8x+2= | | 4y=2x^2+3x-5 | | 5x+(-3)=7 | | 7(3n+4)=8(9n+1)+1 | | 5y=2-(x-7) | | 4.2=1140.8X^5 | | c^2-125=0 | | -4x=12-2x | | -3/7y=4/9 | | 12+3x+9=6x-11-3x |